Air-resistant magnesium-based hydrogen storage material and preparation method thereof
Patent Information
- Application Number
- CN202611190026.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-27
AI Technical Summary
[0009]有鉴于此,本发明旨在解决现有技术中镁基储氢材料在空气中易被毒化且吸放氢动力学性能不足的技术问题,提供一种可抗空气毒化的镁基储氢合金材料及其制备方法
本发明在Mg中添加Ce元素,利用Ce优先于Mg被氧化的特性,在空气暴露条件下Ce优先氧化生成CeO2,有效防止合金颗粒表面形成致密的MgO膜,从而显著提高合金的抗氧化性能。实验表明,本发明的Mg-Ni-Ce合金在空气中暴露60天后仍能保持稳定的吸放氢性能,而Mg在空气中存放5天就发生了明显的性能恶化。
Smart Images

Figure CN122979720A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogen storage materials technology, and relates to a Mg-Ni-Ce based magnesium-based hydrogen storage alloy material resistant to air poisoning and its preparation method. Background Technology
[0002] Hydrogen energy boasts advantages such as high calorific value, being green and pollution-free, and abundant resources, making it an ideal clean energy source. Hydrogen storage technology in hydrogen energy application systems is one of the key factors for the stable and efficient development of hydrogen energy. Hydrogen storage methods are mainly divided into high-pressure gaseous hydrogen storage, cryogenic liquid hydrogen storage, and solid-state hydrogen storage. Among these, solid-state hydrogen storage has attracted much attention due to its large hydrogen storage capacity, safety, efficiency, and reversible recycling. In particular, magnesium has a hydrogen storage density as high as 7.6 wt%, and is abundant and inexpensive, making it widely considered one of the most promising hydrogen storage materials.
[0003] However, magnesium's high hydrogen absorption and desorption temperatures, slow kinetic rates, and high susceptibility to oxidation severely limit its application in practical production and daily life. Particularly concerning oxidation, magnesium readily oxidizes in air to form a dense magnesium oxide (MgO) rock salt structure. This stable oxide film directly hinders the diffusion and transport of hydrogen atoms, significantly reducing its hydrogen storage performance. Maintaining magnesium's hydrogen storage performance requires storage under an inert atmosphere, significantly increasing storage, transportation, and usage costs. Furthermore, in large-scale applications, magnesium-based hydrogen storage materials inevitably experience intentional or unintentional exposure to the atmosphere, necessitating not only optimization of thermodynamic and kinetic properties but also enhancement of oxidation resistance.
[0004] Alloying is an effective method to improve the performance of magnesium-based hydrogen storage materials. Studies have shown that the transition metal element Ni forms a Mg2Ni phase with Mg, which exhibits a significant catalytic effect on the thermodynamic and kinetic properties of magnesium-based hydrogen storage materials. For example, Chinese patent CN121826473A discloses a high-capacity, fast-desorption / absorption magnesium-rich Mg-Ni hydrogen storage alloy, prepared by vacuum melting and ball milling, in which the Mg2Ni phase is uniformly distributed in a continuous network within the Mg matrix, capable of absorbing 6.12 wt% hydrogen within 3 minutes at 260°C. However, this approach does not address the alloy's oxidation resistance and cannot solve the problem of magnesium-based hydrogen storage materials being easily poisoned in air.
[0005] Researchers have attempted to improve the oxidation resistance of magnesium-based hydrogen storage materials by adding rare earth elements. Chinese patent CN116516192A discloses a high-capacity magnesium-based hydrogen storage alloy that requires no activation. By adding alloying elements such as Ce and Zr, an anti-oxidation protective layer is formed on the surface of the magnesium-based hydrogen storage alloy, giving it a certain degree of resistance to air poisoning. However, this method only uses simple smelting and crushing processes, resulting in a coarse alloy microstructure, and the hydrogen absorption and desorption kinetics still need improvement.
[0006] Other studies have explored enhancing antioxidant capacity through the addition of exogenous catalysts. Chinese patent CN112225174A discloses an antioxidant magnesium-based composite hydrogen storage material, which utilizes the redox properties of CeO2 to improve antioxidant performance by ball milling Nb2O5 and CeO2 powders into a Mg-Ni alloy. However, the exogenously added catalyst exhibits poor uniformity of distribution within the matrix and limited bonding strength with the matrix, making it difficult to guarantee catalytic activity and long-term stability.
[0007] In addition, Chinese patent CN112048651A discloses a high-performance, high-capacity hydrogen storage alloy for fuel cells, which is a Mg-Ce-Y-Ni-Co type magnesium-based hydrogen storage alloy with a dual-platform synergistic mechanism. However, its composition is complex and contains expensive Y and Co elements, which increases the material cost. At the same time, this solution does not address the alloy's resistance to air poisoning.
[0008] In summary, there is currently a lack of a technical solution that can effectively address the air poisoning problem of magnesium-based hydrogen storage materials while ensuring high hydrogen storage capacity and rapid hydrogen absorption and desorption kinetics. Summary of the Invention
[0009] In view of this, the present invention aims to solve the technical problems of magnesium-based hydrogen storage materials being easily poisoned in air and having insufficient hydrogen absorption and desorption kinetics in the prior art, and provides a magnesium-based hydrogen storage alloy material resistant to air poisoning and its preparation method.
[0010] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a magnesium-based hydrogen storage material resistant to air poisoning. The magnesium-based hydrogen storage material is a Mg-Ni-Ce hydrogen storage alloy, which is composed of the following components by mass percentage: Ni 10%, Ce 2%-8%, and the balance being Mg.
[0011] Furthermore, the phase composition of the Mg-Ni-Ce hydrogen storage alloy includes Mg phase, Mg2Ni phase and CeMg phase. 12 Mutually.
[0012] Furthermore, the hydrogen storage capacity of the Mg-Ni-Ce hydrogen storage alloy at 300℃ and 3MPa is not less than 5.78wt%.
[0013] Furthermore, after the Mg-Ni-Ce hydrogen storage alloy is cycled 120 times at 300℃ and 3MPa, the hydrogen storage capacity retention rate is not less than 96%.
[0014] Furthermore, the Mg-Ni-Ce hydrogen storage alloy maintains stable hydrogen absorption and desorption performance even after being stored in air for 60 days.
[0015] Meanwhile, the present invention also provides a method for preparing the above-mentioned magnesium-based hydrogen storage material resistant to air poisoning, comprising the following steps: S1. As-cast alloys are prepared by vacuum induction melting, with pure magnesium blocks, Mg-Ni master alloys and Mg-Ce master alloys as raw materials. S2. The as-cast alloy obtained in S1 is subjected to homogenization annealing; S3. The alloy after S2 homogenization treatment is hot forged. S4. Mechanically crush the alloy that has been hot-forged in S3 into powder; S5. The alloy powder obtained in S4 is subjected to ball milling.
[0016] Furthermore, in S2, the homogenization annealing temperature is 450°C, the annealing time is 40 hours, and the annealing is carried out under an argon protective atmosphere.
[0017] Further, in S3, the hot forging process specifically involves: holding the homogenized alloy at 510°C for 1 hour, and then performing hot forging with a deformation of 28%; repeating the above hot forging process once.
[0018] Furthermore, in S5, the ball milling process is wet ball milling, using n-heptane as the solvent, with a ball-to-material ratio of 30:1, a ball milling speed of 200 rpm, a ball milling time of 10 hours, and a ball milling method of intermittent ball milling, with a 10-minute break after each 10-minute ball milling session.
[0019] Furthermore, in S5, the ball milling process is carried out in a sealed ball milling jar. Before ball milling, the ball milling jar is first evacuated and then filled with inert gas.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention adds Ce to Mg, taking advantage of Ce's preferential oxidation over Mg. Under air exposure conditions, Ce preferentially oxidizes to form CeO2, effectively preventing the formation of a dense MgO film on the alloy particle surface, thereby significantly improving the alloy's oxidation resistance. Experiments show that the Mg-Ni-Ce alloy of this invention maintains stable hydrogen absorption and desorption properties after 60 days of exposure to air, while Mg shows significant performance degradation after only 5 days of storage in air.
[0021] This invention effectively refines the alloy microstructure through hot forging, reducing the average particle size of the alloy from 48.2 μm to 33.81 μm, thereby improving the hydrogen absorption and desorption kinetics of the alloy.
[0022] The Mg-Ni-Ce hydrogen storage alloy provided by this invention can achieve a hydrogen storage capacity of 5.78 wt% under conditions of 300℃ and 3MPa, and retain 96% of the hydrogen storage capacity after 120 cycles. It can achieve rapid hydrogen absorption and desorption at 225℃, and has high hydrogen storage capacity, good cycle stability and excellent resistance to air poisoning.
[0023] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description
[0024] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein: Figure 1 The figures show the cycling curves of the alloy at 300℃ and the hydrogen absorption / desorption curves at 225℃. Figure 2 The XRD pattern of the Mg-Ni-Ce alloy; Figure 3 The XRD pattern of the Mg-Ni-Ce alloy in the hydrogen-absorbed state after 60 days of oxidation; Figure 4 Hydrogen absorption data for Mg-Ni-Ce alloy and pure Mg metal after oxidation; Figure 5 SEM image of the ball-milled alloy; Figure 6 SEM image of the hot-forged alloy; Figure 7 This is the first hydrogen absorption curve of the alloy; Figure 8 The hydrogen absorption curve of the alloy at 300℃ and 3MPa; Figure 9 The hydrogen desorption curve of the alloy at 300℃ and 0.01MPa is shown. Detailed Implementation
[0025] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0026] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual images. They should not be construed as limiting the invention. To better illustrate the embodiments of the invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual product dimensions. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.
[0027] Example 1 Please see Figures 1-9 The following provides a detailed description of the specific implementation method of the magnesium-based hydrogen storage alloy material resistant to air poisoning and its preparation method according to the present invention.
[0028] 1. Alloy Preparation Weigh the raw materials according to the following mass percentages: Mg 88%, Ni 10% (in MgNi... 30 Added in intermediate alloy form), Ce 2% (in MgCe) 30 (Added in the form of master alloys). The specific composition of the Mg-Ni master alloy and Mg-Ce master alloy shall be determined by those skilled in the art based on the actual situation to ensure that the final alloy composition meets the above proportion requirements.
[0029] S1. Preparation of cast alloy by vacuum induction melting. Pure magnesium block, Mg-Ni master alloy and Mg-Ce master alloy are placed in a vacuum induction furnace, fully melted and mixed evenly, and then cast into a stainless steel mold. The mixture is then cooled to room temperature with the furnace to obtain alloy billet.
[0030] S2. The obtained as-cast alloy is homogenized and annealed in a vacuum furnace filled with argon gas at a temperature of 450°C for 40 hours. After annealing, it is cooled in the furnace.
[0031] S3. Hold the homogenized alloy at 510℃ for 1 hour, then remove it for hot forging with a deformation of 28%. Repeat this hot forging step once.
[0032] S4. The hot-forged alloy is mechanically crushed into powder.
[0033] S5. Place the alloy powder obtained from mechanical crushing into a ball mill jar, add stainless steel ball milling media and n-heptane solvent, with a ball-to-material ratio of 30:1. After evacuating the ball mill jar, fill it with inert gas and seal it. Place the sealed ball mill jar into a ball mill for ball milling. The ball milling time is 10 hours, with a 10-minute milling interval followed by a 10-minute rest. The ball milling speed is 200 rpm.
[0034] 2. Characterization of alloy microstructure (1) The obtained alloy was analyzed by X-ray diffraction (XRD), and the results are as follows: Figure 2As shown in the figure. The XRD pattern reveals that the Mg-Ni-Ce alloy prepared in this embodiment contains Mg phase, Mg2Ni phase, and CeMg phase. 12 Phase Three Phases.
[0035] (2) The microstructure of the alloy was observed by scanning electron microscopy (SEM). Figure 5 Here is a SEM image of the alloy powder after ball milling. Figure 6 The image shows the SEM image of the alloy after hot forging. The particle size of the alloy was measured, and the results show that the average particle size of the hot-forged alloy is 33.81 μm, while the average particle size of the unforged alloy is 48.2 μm. This indicates that hot forging is beneficial for refining the alloy particles.
[0036] 3. Hydrogen storage performance test (1) Cyclic stability test The alloy was subjected to cyclic hydrogen absorption and desorption tests at 300℃ and 3MPa / 0.01MPa, and the results are as follows: Figure 1 As shown. Figure 1 The cycling curves show that the hydrogen storage capacity of the alloy is 96% after 120 cycles, indicating that the alloy has excellent cycling stability and a hydrogen storage capacity of up to 5.78 wt%.
[0037] (2) Hydrogen absorption and desorption kinetics test Figure 1 The hydrogen absorption and desorption curves of the alloy at 225°C are also shown. Figure 1 As shown, the alloy can rapidly absorb and release hydrogen at 225°C.
[0038] (3) Hydrogen absorption performance test of hot-forged alloy Hydrogen absorption tests were conducted on hot-forged and non-hot-forged alloys at 300℃ and 3MPa. Figure 7 The first hydrogen absorption curve of the alloy is shown. Figure 8 The hydrogen absorption curves of the activated alloy at 300℃ and 3MPa are shown. The alloy after hot forging has better hydrogen absorption performance. (4) Hydrogen release performance test of hot forged alloy Figure 9 The hydrogen release curves of hot-forged and non-hot-forged alloys at 300℃ and 0.01MPa are shown, indicating that the hot-forged alloy has good hydrogen release performance.
[0039] 4. Antioxidant performance test (1) Air exposure experiment The alloy was exposed to air, and the phase composition of the oxidized alloy was analyzed by XRD. For example... Figure 2 As shown, some of the Ce element in the alloy is oxidized to the CeO2 phase, and no MgO phase was found in the XRD data.
[0040] (2) Hydrogen absorption test after oxidation The oxidized alloy was subjected to hydrogen absorption in a hydrogen atmosphere, and then combined... Figure 3 XRD analysis showed that CeO2 was reduced to CeH after hydrogen absorption. 2.29 This indicates that Ce is preferentially oxidized over Mg, thus protecting the Mg matrix from oxidation, and that CeO2 can be reduced to CeH in a hydrogen atmosphere. 2.29 This gives the alloy good oxidation resistance.
[0041] (3) Comparison of long-term air exposure performance Figure 4 Hydrogen absorption data for Mg-Ni-Ce alloys and pure Mg after oxidation are shown. Figure 4 As shown, the Mg-Ni-Ce alloy can still maintain stable hydrogen absorption and desorption properties after being stored in air for 60 days, while pure Mg shows significant performance deterioration after being stored in air for 5 days.
[0042] II. Comparative Example Using pure Mg as a comparative example, the oxidation resistance of Mg-Ni-Ce alloy and pure Mg was compared. Pure Mg showed significant performance degradation after being stored in air for 5 days, while the Mg-Ni-Ce alloy of Example 1 maintained stable hydrogen absorption and desorption properties after being stored in air for 60 days.
[0043] Using alloys of the same composition but not hot-forged as comparative examples, such as... Figure 7 , 8 As shown in Figures 9 and 1, the alloy after hot forging has better hydrogen absorption and desorption properties.
[0044] III. Variations Variation Example 1 Based on Example 1, the alloy composition ratio was adjusted.
[0045] Specifically, the mass percentage of Ce can be adjusted within the range of 2% to 8%, the mass percentage of Ni is 10%, and Mg is the balance.
[0046] When the Ce content is below 2%, the alloy contains relatively little Ce, resulting in poor resistance to air poisoning; when the Ce content is above 8%, the alloy contains significant Ce and Mg content. 12 Excessive phase content and coarse structure lead to a decrease in hydrogen storage capacity and performance.
[0047] Therefore, controlling the Ce content at 2% to 8% can ensure high hydrogen storage capacity while also taking into account catalytic activity and resistance to air poisoning.
[0048] Variation Example 2 Based on Example 1, the ball milling process parameters were adjusted.
[0049] Specifically, the ball-to-material ratio can be adjusted within the range of 30:1 to 40:1, the ball mill speed can be adjusted within the range of 200 to 350 rpm, and the ball milling time can be adjusted within the range of 8 to 12 hours.
[0050] When the ball-to-powder ratio is less than 30:1, the powder refining efficiency is insufficient; when the ball-to-powder ratio is greater than 40:1, it is easy to introduce too many grinding ball wear impurities.
[0051] When the ball mill speed is below 200 rpm, the ball milling energy is insufficient and the powder particle size is large; when the ball mill speed is above 350 rpm, the powder is prone to cold welding and agglomeration.
[0052] By controlling the above parameter range, alloy powder with uniform particle size and suitable activity can be obtained.
[0053] IV. Technical Effects Based on the above embodiments and comparative examples, the technical effects of the present invention can be summarized as follows: In terms of combating air pollution, such as Figure 4 As shown, the Mg-Ni-Ce alloy of the present invention maintains stable hydrogen absorption and desorption properties after being stored in air for 60 days, while pure Mg shows significant performance deterioration after being stored in air for 5 days, confirming the protective effect of Ce preferential oxidation to CeO2 on the Mg matrix.
[0054] In terms of organizational refinement, combined with Figure 5 and Figure 6 The SEM results showed that hot forging reduced the average particle size of the alloy from 48.2 μm to 33.81 μm, effectively improving the hydrogen absorption and desorption kinetics of the alloy.
[0055] In terms of hydrogen storage performance, such as Figure 1 and Figure 8 As shown, the alloy has a hydrogen storage capacity of 5.78 wt% at 300℃ and 3MPa, and a capacity retention rate of 96% after 120 cycles. It can achieve rapid hydrogen absorption and desorption at 225℃, and has high hydrogen storage capacity, good cycle stability and excellent resistance to air poisoning.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A magnesium-based hydrogen storage material resistant to air poisoning, characterized in that, The magnesium-based hydrogen storage material is a Mg-Ni-Ce hydrogen storage alloy, which, by mass percentage, consists of the following components: Ni 10%, Ce 2%-8%, and the balance being Mg.
2. The magnesium-based hydrogen storage material resistant to air poisoning according to claim 1, characterized in that, The phase composition of the Mg-Ni-Ce hydrogen storage alloy includes Mg phase, Mg2Ni phase and CeMg phase. 12 Mutually.
3. The magnesium-based hydrogen storage material resistant to air poisoning according to claim 1 or 2, characterized in that, The hydrogen storage capacity of the Mg-Ni-Ce hydrogen storage alloy is not less than 5.78 wt% under the conditions of 300℃ and 3MPa.
4. The magnesium-based hydrogen storage material resistant to air poisoning according to claim 1 or 2, characterized in that, The Mg-Ni-Ce hydrogen storage alloy retains a hydrogen storage capacity of no less than 96% after 120 cycles at 300℃ and 3MPa.
5. The magnesium-based hydrogen storage material resistant to air poisoning according to claim 1 or 2, characterized in that, The Mg-Ni-Ce hydrogen storage alloy can maintain stable hydrogen absorption and desorption performance after being stored in air for 60 days.
6. A method for preparing a magnesium-based hydrogen storage material resistant to air poisoning as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. As-cast alloys are prepared by vacuum induction melting, with pure magnesium blocks, Mg-Ni master alloys and Mg-Ce master alloys as raw materials. S2. The as-cast alloy obtained in S1 is subjected to homogenization annealing; S3. The alloy after S2 homogenization treatment is hot forged, with a deformation of 28%; S4. Mechanically crush the alloy that has been hot-forged in S3 into powder; S5. The alloy powder obtained in S4 is subjected to ball milling.
7. The preparation method according to claim 6, characterized in that, In S2, the homogenization annealing temperature is 450°C, the annealing time is 40 hours, and the annealing is carried out under an argon protective atmosphere.
8. The preparation method according to claim 6, characterized in that, In S3, the hot forging process specifically involves: holding the homogenized alloy at 510°C for 1 hour, and then performing hot forging with a deformation of 28%; repeating the above hot forging process once.
9. The preparation method according to claim 6, characterized in that, In S5, the ball milling process is wet ball milling, using n-heptane as the solvent, with a ball-to-material ratio of 30:1, a ball milling speed of 200 rpm, a ball milling time of 10 hours, and a ball milling method of intermittent ball milling, with a 10-minute break after each 10-minute ball milling session.
10. The preparation method according to claim 6, characterized in that, In S5, the ball milling process is carried out in a sealed ball milling jar. Before ball milling, the ball milling jar is first evacuated and then filled with inert gas.
Citation Information
Patent Citations
High-performance high-capacity hydrogen storage alloy for fuel cell and preparation method of hydrogen storage alloy
CN112048651A
Antioxidant magnesium-based composite hydrogen storage material and preparation method thereof
CN112225174A
Activation-free high-capacity magnesium-based hydrogen storage alloy and preparation method thereof
CN116516192A
High-capacity magnesium-rich Mg-Ni hydrogen storage alloy capable of rapidly absorbing and desorbing hydrogen and preparation method of magnesium-rich Mg-Ni hydrogen storage alloy
CN121826473A